IMPACT OF HUMAN RESOURCE SYSTEMS AND PRACTICES ON ATTITUDES TOWARD CAREER DEVELOPMENT PROGRAMS IN THE BANKING SECTOR OF JORDAN - Rawashdeh, Abas Salem (European Scientific Journal, ESJ, 2013)
Purpose: The purpose of this paper is to examine the effects of human resource systems and practices, on attitudes toward career development programs. Specifically it aims to investigate whether the human resource systems and practices being adopted and employed by the banking sector in Jordan, impact attitudes toward career development programs. Methodology: The main instrument of research used in this study was the survey questionnaire which consisted of two parts. The first part was focus on human resource systems and practices linked to career development programs. The second part inquired into how the subject banks view career development programs. Data gathered were statistically treated using arithmetic weighted mean, and it was interpreted based on the Likert scale, in testing the hypothesis multiple regression was used. Findings: The results showed that the following human resource systems, job analysis, human resource planning, recruitment and selection, performance appraisal, and promotion were noted to be linked with career development programs, there was positive views regarding what career development programs can do. Regarding the impact of human resource systems and practices on attitudes toward career development programs, six proposition were developed, result of the multiple regression test showed that there were a positive effect of the following human resource systems; job analysis, human resource planning, recruitment and selection, performance appraisal, and promotion, and there was no positive effect of the employee assistance programs on attitudes toward career development programs.